EVALUATING THE ROLE OF L1 IN TEACHING RECEPTIVE SKILLS AND GRAMMAR IN EFL CLASSES - Hidayati, Istiqlaliah Nurul (Universitas Pendidikan Indonesia, 2012)
Abstract: The debate over the use of Bahasa Indonesia and English has been an unsolved issue. Some teachers still lack confidence in using Bahasa Indonesia in their teaching to promote classroom interaction. Classroom interaction is important since the more engaged the students are, the more successful the material delivery will be. Hence this study was aimed at finding out whether or not teacher’s use of Bahasa Indonesia in teaching receptive skills of language and grammar contributes to classroom interaction and investigating the benefits of the use of Bahasa Indonesia in EFL classes as perceived by the teachers and the students. Six classes of different majors and six English lecturers from a polytechnic in Bandung participated in the study. The data were collected through questionnaires, interview, and classroom observation. The findings support the idea that teachers’ use of Bahasa Indonesia judiciously promotes classroom interaction. Both students and teachers found the benefits of the use of Bahasa Indonesia in the classroom only when it was needed. However, some teachers still overused Bahasa Indonesia in the EFL classrooms. Keywords: teachers and students’ perceptions, classroom interaction, English (L2), Bahasa Indonesia (L1), English as a Foreign Language Teaching